Community Participation: A Cementing Process, Theorizing Various Dimensions and Approaches - Johar, Nirmala (Penerbit Universiti Sains Malaysia, 2017)
One of the hallmarks of urban planning in recent decades has been focused on slum upgrading through improvements in service delivery, better housing and employment policies. This paper explores community participation as an instrument in providing affordable housing for urban poor in India and abroad. Community Participation (CP) creates an appreciation of how people can present their claims in front of development agencies. There is an increasing recognition that the urban development policy framework be inclusive of the people residing in the slums and informal settlements. It is argued in the available literature that community participation and active involvement of the benefciaries is critical to the success of a programme as people’s participation advances their interests, needs, and aspirations in the development discourse. Collaborative initiatives give rise to an enabling approach through which we can achieve a more effective mobilization of community resources and skills to complement public resource allocations. We can increase well-being of deprived section of society by shifting from a needs-based approach to asset based community development. This paper focuses on conceptual framework of community participation along with successful examples of participatory models adopted by the Indian Institute of Human Settlement and Ministry of Housing and Urban Poverty Alleviation, Government of India to accomplish the target of Housing for All. The discussion will be limited to Community Participation in Slum Improvement Schemes. Various paradigms of Slum Improvement will be brieﬂy discussed. The scope of participatory approach will be evaluated with respect to ladder of participation as established by Sherry Arnstein and Marisa B. Guaraldo Choguill. The paper also makes recommendations within administrative boundaries of institutional framework of local body and provide valuable lessons that can be applied to the implementation of the new urban Sustainable Development Goals.